2020
DOI: 10.1136/bmjhci-2019-100099
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of healthcare professionals about the adoption and use of EHR in Gulf Cooperation Council countries: a systematic review

Abstract: IntroductionElectronic health records (EHRs) can improve the quality and safety of care. However, the adoption and use of the EHR is influenced by several factors, including users’ perception.ObjectivesTo undertake a systematic review of the literature to understand healthcare professionals’ perceptions about the adoption and use of EHRs in Gulf Cooperation Council (GCC) countries in order to influence the implementation strategies, training programme and policy development in the GCC region.MethodA systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
4
9
0
Order By: Relevance
“…However, leadership is recommended ( Cawthon et al, 2014 ) because training in HL measurement and support at all stages of implementation is necessary ( Cawthon et al, 2014 ; Sand-Jecklin et al, 2017 ). These findings are supported by other research that has reported positively on healthcare professionals’ participation in learning about HL and the use of HL-related tools ( Alanazi et al, 2020 ; Asan et al, 2015 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, leadership is recommended ( Cawthon et al, 2014 ) because training in HL measurement and support at all stages of implementation is necessary ( Cawthon et al, 2014 ; Sand-Jecklin et al, 2017 ). These findings are supported by other research that has reported positively on healthcare professionals’ participation in learning about HL and the use of HL-related tools ( Alanazi et al, 2020 ; Asan et al, 2015 ).…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, all included studies reported that HL assessments were included in the EHRs; this is important since EHRs help to improve healthcare organisation workflows ( Ahmed et al, 2020 ; Alotaibi & Federico, 2017 ), communication between healthcare professionals from different contexts and countries ( Asan, Young, Chewning, & Montague, 2015 ) and documentation accuracy and the likelihood of using documentation ( Ahmed et al, 2020 ). However, using EHRs requires healthcare professionals to be computer literate, as well as conditions that facilitate the use of EHRs, such as adequate numbers of computers and tablets and sufficient personnel and software to ensure data entry accuracy ( Alanazi, Butler-Henderson, & Alanazi, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the perceptions of health care professionals about EMR adoption in the Gulf Cooperation Council countries has provided a lack of training as a major barrier to EMR adoption. 15 Similarly, evidence from western Canada states that the lack of proper practical training and support for EMR systems has affected the success of EMR implementation. 16 In another study from India, two-thirds of medical professionals cited a lack of EMR training as a barrier to EMR adoption.…”
Section: Discussionmentioning
confidence: 99%
“…This exploration is consistent with a systematic review of the perceptions of health care professionals on EHR adoption in the Gulf Cooperation Council countries, in which negative perception is a major challenge to adopt an EHR. 15 This is a good explanation for the need for professionals to be aware of the EMR system before implementing it so that they have a good attitude and develop their readiness for better adaptation of the system.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for collaboration between technology experts, physicians and citizens ( 25 ), which is especially challenging in a region with a significant reliance on a foreign healthcare workforce and the related training issues ( 4 , 6 ). The existence of electronic health records is generally seen as a positive development to aid adoption of precision medicine, with barriers informing changes in strategy ( 35 ). Telemedicine, involving remote delivery of care, is becoming more common in the GCC region, with new initiatives such as the Saudi Telemedicine Unit of Excellence now established ( 36 , 37 ).…”
Section: Digital Health Trends In the Gcc Regionmentioning
confidence: 99%